INSTITUTIONAL MECHANISMS FOR MODERNIZING PUBLIC ADMINISTRATION OF EDUCATION IN THE CONTEXT OF DIGITALIZATION: CHALLENGES AND PROSPECTS - Protsenko, Valentyna (Public Management and Policy, 2025)
The article examines the institutional mechanism for the modernization of public education management in Ukraine in the context of digitalization, with a special focus on regulatory and legal principles, organizational and managerial tools, key challenges and strategic vectors of development. The purpose of the study is to substantiate and systematize the institutional mechanisms for the digital transformation of public education management, identify the main barriers to digitalization, and formulate practical recommendations for building a sustainable digital architecture of the education sector taking into account European standards. The methodological basis is based on a systematic analysis of the regulatory and legal acts of Ukraine in the field of digital transformation of education. The methods of theoretical generalization, comparative and institutional analysis, modeling of management processes, as well as author’s tabular and graphical models for the visualization of organizational and managerial measures and strategic directions of modernization are used. The obtained scientific results show that the regulatory framework has already formed the basic digital infrastructure, but its effectiveness is limited by uneven access, low level of digital maturity of regions, shortage of qualified personnel, cybersecurity risks and institutional resistance to transformation processes. The need to transition to a hybrid centralized-decentralized management model and the introduction of approaches focused on adaptivity and agility is substantiated. Organizational and management proposals and strategic directions of institutional modernization are formed, which systematize key tools and indicators of achieving target indicators. The practical significance of the study lies in the development of specific organizational and management measures and a strategic model that can be implemented by the Ministry of Education and Science, regional state administrations and educational institutions to intensify digital transformation. Prospects for further scientific explorations are associated with empirical verification of the proposed model at the regional level and assessment of the impact of artificial intelligence on the processes of managerial decision-making in the educational sector. Special attention is required to develop mechanisms for the full integration of Ukrainian digital educational systems into the European digital space.